Sodium alginate-based composite microspheres for controlled release of pesticides and reduction of adverse effects of copper in agricultural soils. (February 2023) - Du, Yu; Zhang, Qizhen; Yu, Manli; Jiao, Bin; Chen, Fuliang; Yin, Mingming
Abstract: Excessive copper (Cu) concentrations pose significant health risks to both plants and humans. In this study, sodium alginate (SA)-gelatin (GEL)-polyvinyl pyrrolidone (PVP)- embedded dinotefuran (DIN) microspheres were prepared using spray-drying technology. The loading content and encapsulation efficiency of optimal microspheres determined by physical modifications were 19.77% and 99.32%, respectively. In addition, the microspheres showed variable stimuli-responsive controlled release capacities in different temperatures and types of soil, as well as showed better control efficiency of larvae of Protaetia brevitarsis at pesticide application in the early stage, with the potential ability to control pest outbreaks at high temperatures. In addition, blank microspheres improved the growth and physiological activity of cucumber seedlings, reduced copper content in leaves, increased soil nutrient content, and prevented soil acidification. Further, the use of blank microspheres increased the relative abundance of soil beneficial functional bacteria communities, which mediate heavy metal (HM) immobilization/tolerance and promote plant growth. Redundancy analysis (RDA) and Spearman correlation analysis showed that these beneficial functional bacteria were mainly positively correlated with soil EC, A-N, and N–N. In summary, this study showed that the technique of combining physically modified carrier materials with pesticides has the potential to reduce Cu contamination in the surrounding agricultural soil during pesticide application, thereby reducing Cu uptake by crops. Graphical abstract: Image 1 Highlights: A temperature and soil type sensitive controlled-release system were developed. b-MS reduced Cu content and enhanced plant growth properties. Improved soil properties, increased soil nutrients, and inhibited soil acidification. Increased heavy metal immobilization/tolerance and plant growth promotion bacteria. The beneficial bacteria were mainly positively correlated with soil EC, A-N and N–N.